Dampak Kebijakan Harga dan Impor Beras terhadap Nilai Tukar Petani di Pantai Utara Jawa Barat - Rahim, Manat (Jurnal Trikonomika, 2010)
The objectives of the research are to know the impact of price policy and the import of rice toward the market level, the price of paddy in the consumer level and farmers term of trade in the Northem Coast Of West Java Province. The data used in this research is secondary and primary data in the form of time series that provided by Central Bureau of Statistic and respondents in a field survey. Analysis method used in the study is ordinary least square method with log transformation. The result of this research indicated that the price policy affected significantly and positively the price of paddy in the farm level. The price policy affected significantly and positively upon the price of price at consumer level. The import of rice affected significantly and negatively upon the price off paddy at the farm level. The import of rice significantly and negatively affected the price of rice at consumer level. The price policy affected significantly and positively upon farmers term of trade. The import of rice affected significantly and negatively upon farmers terms of trade.